Robust anti-tubercular profile of Solanum virginianum extract in enhancing isoniazid bioavailability and curtailing stress tolerance in Mycobacterium smegmatis - Balkrishna, Acharya; Joshi, Monali; Kabdwal, Manisha; Tomer, Meenu; Lochab, Savita; Varshney, Anurag (Frontiers in Microbiology, 2024)
Tuberculosis, a centuries-old human health menace, remains elusive despite several ambitious global initiatives. The formidable survival mechanisms employed by the causative agent, Mycobacterium tuberculosis (Mtb), coupled with the limited bioavailability of anti-tubercular drugs, contribute to the development of multi-drug resistant strains and drug-associated hepatotoxicity. In addressing these challenges, it is imperative to complement the use of antitubercular drugs with adjunct therapy, particularly leveraging herb-drug synergism to enhance drug bioavailability. This study explores the potential of Solanum virginianum as adjunct therapy that could enhance the efficacy of anti-tubercular drugs. We characterized the hydro-methanolic extract of Solanum virginianum (SVE) for phytochemicals using HPTLC and UHPLC. Comparative growth profiles and CFU assays demonstrate the inhibitory effect of SVE on the growth and viability of mc 2 155 under normal and in vitro stress conditions. Additionally, scanning electron microscopy (SEM) depicts altered microarchitecture, and TLC-based classical metabolomic approaches demonstrate SVE-induced compromised cell wall integrity in the bacilli. Utilizing UPLC/QToF-MS based targeted metabolomics technique, isoniazid (INH) was quantified in the complex biological matrix of mc 2 155. The study demonstrates that SVE enhances the bioavailability of INH inside the bacilli, thereby augmenting the susceptibility of mc2155 towards INH. THP-1 infection experiments with adjunct treatment of SVE and INH demonstrated markedly reduced survival of intracellular bacilli. The study also uncovers the hepatoprotective potential of SVE in HepG2 cells. Our study lays the groundwork for future research on the antimycobacterial properties of SVE against pathogenic Mtb strains. Collectively, these findings suggest SVE as a potent candidate for adjunct-anti-tubercular therapy.